2013
DOI: 10.1139/cjpp-2012-0295
|View full text |Cite
|
Sign up to set email alerts
|

Redox-inflammatory synergy in the metabolic syndrome

Abstract: Metabolic syndrome (MetS) comprises interrelated disease states including obesity, insulin resistance and type 2 diabetes (T2DM), dyslipidemia, and hypertension. Essential to normal physiological function, and yet massively damaging in excess, oxidative stress and inflammation are pivotal common threads among the pathologies of MetS. Increasing evidence indicates that redox and inflammatory dysregulation parallels the syndrome's physiological, biochemical, and anthropometric features, leading many to consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 108 publications
1
34
0
Order By: Relevance
“…The diminished sulfotransferase expression and activity in liver disease could be related to inflammation (Bryan et al, 2013). Previous studies have shown the induction of proinflammatory cytokines with diet-induced obesity, which reduces levels of drug metabolism enzymes, including sulfotransferases (Ghose et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The diminished sulfotransferase expression and activity in liver disease could be related to inflammation (Bryan et al, 2013). Previous studies have shown the induction of proinflammatory cytokines with diet-induced obesity, which reduces levels of drug metabolism enzymes, including sulfotransferases (Ghose et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These cells secrete so-called cytokines and attract macrophages, which also secrete these cytokines that are also secreted during inflammatory processes, hence overweight people of the 'apple type' are in a chronic inflammatory state with high levels of circulating cytokines like tumor necrosis factor α (TNF α), interleukin 6 (IL6), leptin, adiponectin and others [67]. Visceral obesity results not only in increased cholesterol production, particularly of the unhealthy LDL and the very unhealthy triglycerides in VLDL, but also high oxidative stress and elevated serum concentrations of the inflammation marker C-reactive protein (CRP) [70][71][72][73]. This increases the risk for arteriosclerosis with the consequence of increased heart attacks and strokes.…”
Section: Another Rediscovered Alternative To Prevent or Treat Postmementioning
confidence: 99%
“…Various pro-inflammatory transcription factors, including nuclear factor κB (NF-κB) and activator protein-1 (AP-1), can induce the production of ROS, causing the release of inflammatory cytokines. This in turn enhances oxidative stress, thus setting a vicious cycle [29]. While it is important that zinc also attenuates oxidative stress by acting as an anti-inflammatory nutrient, the precise mechanism remains unclear.…”
Section: Biochemical Aspectsmentioning
confidence: 99%